Improving Production, Chlorophyll a and Carotenoids Contents of Gracilaria sp. with Liquid Organic Fertilizer from Alginate Waste - Ervia Yudiati; Ali Djunaedi; Dea Shinta Kharisma Adziana; Ayunda Ainun Nisa; Rabia Alghazeer (Marine Science Department Diponegoro University, 2021)
Chlorophyll is a photosynthetic pigment, used in the food sector as a natural dye in food. Carotenoids is used in the health sector to prevent several disease in humans. The production and pigment contents are influenced by nutrient availability. The aim of this study was to increase the production of chlorophyll a and carotenoids contents in Gracilaria sp. Seaweed obtained from Demak aquaculture ponds, then cultivated in aquarium for 28 days.Alginate from Sargassum sp. waste fertilizer was prepared by adding some compounds, fermented by commercial Saccharomyces cerevisiae. Five different treatments (FB (basal formulation: 75 g alginate waste + 22.5mL molase + 7.5 g S. cerevisiae + 250 mL aquadest)), FBL (basal formulation+100% Lamtoro leaves), FBLU (basal formulation+50%Lamtoro leaves+50% carapace shrimp waste), FBU (Basal formulation + 100% carapace shrimp waste) and control-without fertilizer) was applied. Analysis of pigments was determined using the spectrophotometric method. The research design was CRD with 4 treatments and a control. Data were analyzed using Kruskal-Wallis statistical analysis. The result showed that fertilization in culture media could increase the production (DW) and pigment contents. The highest levels of dry weight, chlorophyll a and carotenoids (P<0.05) were resulted from FBLU ie. 6.58 ± 0.07g dry weight; 5.47 mg.L-1 and 0.16 µmol.L-1.The application of organic fertilizer from alginate extract waste to Gracilaria sp. culture media had a significant effect towards growth, dry weight, chlorophyll a and carotenoids pigments content. This inexpensive fertilizer expected to be the solution of green and zero waste management which provide the enviromentally friendly fertilizer.